THE STUDY OF SME’S PROFITABILITY AND ITS RELATION TO THE AVAILABILITY OF ELECTRICAL ENERGY IN TELUK WONDAMA REGENCY - Irawantho Irawantho; Alimuddin Alimuddin; Nursini Nursini (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2019)
This research aimed to investigate the effect of electrical energy costs, the business capital, and the total of the laborers on the profits of the Micro Small and Medium Enterprises in Teluk Wondama Regency.This research used the regression equation. The Objects of the study were Micro Small and Medium Enterprises who were business actors who were impacted doe to the establishment of the cooperation between the Government of Teluk Wondama Regency and PT. PLN in term of supply of the electrical energy. The data were collected using the technique of questionnaires distributed to 90 micro small and medium enterprises. The types of data used were the primary data. The analysis model used in this research was the multiple linear regression.The research result indicated that (1) The electrical costs had a positive and significant effect on the profits of SME in Teluk Wondama Regency; (2) The business capital had a positive and significant effect on the profits of SME in Teluk Wondama Regency; (3) The number of laborers had a positive and significant effect on the profits of SME in Teluk Wondama Regency. The roles of the three factors together had the effect of 46.5%, while the rest of about 53.5% was determined by other factors.